Effect of casting parameters on the microstructure and mechanical properties of squeeze cast A380 aluminum die cast alloy - Lus, H. Murat (REDAKCIA KOVOVE MATERIALY, 2012)
A380 Al-Si-Cu die casting alloy is the most common of all die casting Al alloys and is used especially in the automotive industry due to the best combination of utility and cost. A high percentage of these components are produced by a high pressure die casting process; however, the quality and performance of these components need to be improved. Therefore, different approaches to component-making have been introduced such as semi-solid forming or squeeze casting over the last four decades. In the present study, direct squeeze casting of A380 alloy as a function of applied pressure was investigated. Applied pressures from 10 MPa to 50 MPa were considered and compared with gravity die cast samples. SDAS values ranging from 5.70 mu m to 10 mu m have been obtained by squeeze casting whereas 13.70 mu m was found in gravity die casting. Density measurements and mechanical tests show us that the porosity level and presence of micro-voids were greatly decreased with increasing pressure while ultimate tensile strength and elongation increased in squeeze cast parts.
Keywords: squeeze casting; A380 alloy; Al-Si-Cu alloy; dendrite arm spacing; PRESSURE; Materials Science; Metallurgy & Metallurgical Engineering